3D Printed Ti3C2Tx MXene/Cellulose Nanofiber Architectures for Solid‐State Supercapacitors: Ink Rheology, 3D Printability, and Electrochemical Performance. (16th December 2021) - Zhou, Guoqiang; Li, Mei‐Chun; Liu, Chaozheng; Wu, Qinglin; Mei, Changtong
Abstract: Direct ink writing technology is capable of using 2D MXene to construct 3D architectures for electrochemical energy storage (EES) devices that are normally difficult to achieve using conventional techniques. However, to meet specific rheological requirements for 3D printing, a large amount of MXene is needed in the ink, resulting in a severe self‐restacking structure after drying. Herein, a series of cellulose nanofibers (CNFs) with different morphologies and surface chemistries are applied to enhance the rheology of the MXene‐based inks with exceptional 3D printability. Various 3D architectures with superior shape fidelity and geometric accuracy are successfully printed using the optimized hybrid ink at a low solid content, generating self‐standing, hierarchically porous structures after being freeze‐dried, which improves surface area accessibility, ion transport efficiency, and ultimately, capacitive performance. A solid‐state interdigitated symmetrical supercapacitor is further 3D printed, which delivers an areal capacitance of 2.02 F cm −2 and an energy density of 101 μWh cm −2 at a power density of 0.299 mW cm −2, and maintains a capacitance retention rate of 85% after 5000 cycles. This work demonstrates the integration of 1D CNFs and 2D MXene in 3D printing technology to prepare customized, multiscale, and multidimensional architectures for the next generation of EES devices. Abstract : By rationally controlling the dimension and surface chemistry of cellulose nanofibers (CNFs), CNFs are successfully applied as rheology modifiers to formulate viscoelastic, 3D printable MXene‐based ink at a low solid concentration of 8 wt%. The freestanding, hierarchically porous MXene‐based electrode architectures can be achieved by 3D printing and freeze‐drying, which holds great potential in electrochemical energy storage devices.